The Effect of Charter School Legislation on Market Share - Kúscová, Simona; Buckley, Jack (Education Policy Analysis Archives, 2004)
Many proponents of school choice use the claim of the market’s capability to enhance efficiency and improve performance to call for its expansion. But no markets are perfectly competitive, and the local market for public goods is filled with institutional arrangements that make it differ from the neoclassical ideal. In this paper, we look at a particular institution—the provisions of charter school legislation—and assess how it affects the ability of charter schools to gain market share. Using data from the 36 states that had passed charter legislation by 2000, and controlling for a variety of other factors, we estimate a model of the effects of various provisions in the charter laws on charter school market share. We find that two such provisions, one concerning the sponsorship of charters and another their funding sources, appear to have a strong effect on the market share of charter schools.